Who is the bilingual student? : Concepts available in the Political-Pedagogical Project of schools that call themselves bilingual - Mizukami, Adriana Carvalho; Lodi, Ana Cláudia (The ESPecialist, 2023)
This article seeks to understand, through the analysis of political-pedagogical projects of two schools (A and B) who called themselves bilingual, and who is the student that they intend to form. It was observed that, while the proposal of school A aimed for students to become bilingual from the experience of languages in the school environment, moving between them and putting them in constant contact, the proposal of school B was based on the assumption that the bilingual student is someone who learns a foreign language independently of the native language, therefore in a monolingual environment. It is thus concluded that, just as there are different ways to understand bilingualism, there is also no single way to think about bilingual education. In common between the proposals there is only the promise of a better future for those who know a foreign language, especially English.